# What is the solution of the equation (x^3 - x)^1/2 + (2x - 1)^1/2 = (x^3 + x - 1)^1/2?

*print*Print*list*Cite

Here we need to solve the equation (x^3 - x)^1/2 + (2x - 1)^1/2 = (x^3 + x - 1)^1/2 for x.

We go about it in the following way. First eliminate the power 1/2 that has been applied to all the terms. This can be done by taking the square of both the sides.

=> [(x^3 - x) ^ (1/2) + (2x - 1) ^ (1/2)] ^2 = [(x^3 + x - 1) ^ (1/2)] ^2

=> (x^3 - x) + (2x - 1) +2*(x^3 - x) ^ (1/2) *(2x - 1) ^ (1/2) = (x^3 + x - 1)

=> x^3 – x + 2x – 1 + 2*(2x^4 – x^3 – 2x^2 + x) ^ (1/2) = x^3 + x -1

cancel the common terms

=> 2*(2x^4 – x^3 – 2x^2 + x) ^ (1/2) = 0

=> (2x^4 – x^3 – 2x^2 + x) ^ (1/2) = 0

square both the sides

=> 2x^4 – x^3 – 2x^2 + x = 0

=> x (2x^3 – x^2 – 2x + 1) = 0

=> x [x^2(2x-1) -1(2x-1)] = 0

=> x(x-1) (x+1) (2x-1) =0

=> x = 0 or x-1=0 or x+1=0 or 2x-1=0

=> x = 0 or x = 1 or x = -1 or x = 1/2

**Therefore the solutions for x are 0, 1, -1 and 1/2.**